Developing and validating happiness instrument based on Al-Ghazali's concept - Ateerah Abdul Razak@Mohamed
A study on happiness has grown dramatically throughout these decades. However, Western and Islamic concepts of happiness have different point of view. Happiness is an important notion in Islam and for human well-being, and there is a need to build a scale to measure to what extent a Muslim believes that he has secured happiness in the afterlife. Nevertheless, there is a lacking of studies that examine its psychometric properties in Islamic perspective. Thus, this study is conducted to identify factors that contribute to Muslim's happiness based on al-Ghazali' concept. The researcher developed conceptual framework based on al-Ghazali's theory of happiness.It employs Exploratory Factor Analysis (EF A in order to provide the information about the constructs, and Confirmatory Factor Analysis (CF A) to validate the constructs of psychometric properties of self developed instrument. Thi i to empirically evaluate a specified set of factors affecting that construct in a predicted manner. It encompasses several aspects such as religious knowledge, practices, and individual aspects as drivers of happiness and they act as independent variables. This study used quantitative method; it was carried out by di tributing questionnaires to respondents face-t -face. From the qu tionnaires collected, 500 respondents were selected using a convenienc sampling meth d, and the respondents consist of University tudents, residents in several religious institutions and also the general public. They were of various ages representing a proportion of each respective location. The findings were then analysed using SPSS and PLS. Based on structural equation modelling, the study found that religious knowledg practices, and individual constructs have significant relationship with happiness. The average variance extracted (AVE) values ranges between 0.501 - 0.615, which is an acceptable valid range. It can be observed that there is a significant relation between individual construct and happiness (t=2.817, p<0.005), practices and happiness (t=6.805, p<O.OOO), and religious knowledge and happiness (t=3.947, p<O.OOO). Moreover, the positive sign implies that there is a direct relationship between the dependent and independent variables. This study prove that religious knowledge, practices and individual constructs are interrelated in contributing to a Muslim's happiness. In addition, it shows the importance of development of reliable and valid measures in empirical studies within an Islamic context. The results of this study are useful for Muslim to measure whether or not he/she acquires happiness based on Islamic perspective. Consequently, the current research also will benefit researchers, educators, academicians, and students of religious studies to apply psychometric properties based on Islamic perspective of happiness.